2017
DOI: 10.1055/s-0037-1599228
|View full text |Cite
|
Sign up to set email alerts
|

Association of Midfacial Fractures with Ophthalmic Injury

Abstract: The aim of this study is to evaluate the incidence of ophthalmic complications following midfacial fractures and investigate its relation to surgical or nonsurgical treatment. This article is a retrospective study, describing the spectrum and incidence of ophthalmic injury in 106 patients presenting with midfacial fractures at the Department of Oral and Maxillofacial Surgery of the University Hospitals Leuven over a period of 16 months (January 2013 to April 2014). The mean age of the patients was 45.6 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In literature, between 38.7% and 95.7% of patients with midfacial fractures also have ocular injuries. [ 4 6 11 ] In our study, 85.5% of the patients with midfacial injuries had ocular injuries, showing the importance of proper diagnosis of ocular injuries in patients with injuries to the midface. With respect to demographics, there were more males (83.8%) than females (16.2%), with most patients (38.7%) aged between 21 and 30 years of age [ Table 1 ].…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In literature, between 38.7% and 95.7% of patients with midfacial fractures also have ocular injuries. [ 4 6 11 ] In our study, 85.5% of the patients with midfacial injuries had ocular injuries, showing the importance of proper diagnosis of ocular injuries in patients with injuries to the midface. With respect to demographics, there were more males (83.8%) than females (16.2%), with most patients (38.7%) aged between 21 and 30 years of age [ Table 1 ].…”
Section: Discussionmentioning
confidence: 61%
“…This is similar but much higher than other reports where between 43.3% and 77.0% of midfacial injuries were due to RTAs. [ 7 9 10 11 ] While the second most common etiology in our study was assault or interpersonal violence (IPV) (4.7%), followed by animal injury (2%) and falls (1.3%) [ Table 1 ], most other studies[ 7 9 10 11 ] reported falls (23.5%–32.0%), followed by IPV (6.9%–21.0%).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations